The Type and Timing of Child Maltreatment as Predictors of Adolescent Cigarette Smoking Trajectories. (1st April 2020) - Yoon, Susan; Dillard, Rebecca; Kobulsky, Julia; Nemeth, Julianna; Shi, Yang; Schoppe-Sullivan, Sarah
Abstract: Background: There is limited research examining the association between child maltreatment and cigarette smoking as a specific type of adolescent substance use, and research examining high-risk samples and variations based on maltreatment type and timing remain sparse. Objectives: The primary aim of the study was to examine the relationship between child maltreatment and cigarette smoking trajectories. Methods: Latent class growth analysis and multinomial logistic regression were performed on 903 youth drawn from the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN). Results: Three distinct classes of cigarette smoking trajectories were identified: (1) Stable no/low cigarette use (61%); (2) Gradually increasing cigarette use (30%); and (3) Sharply increasing cigarette use (9%). Physical abuse during early childhood and adolescence predicted membership in the sharply increasing cigarette use class. Neglect during early childhood predicted membership in the gradually increasing cigarette use class. Conclusions: Findings suggest that interventions for adolescent cigarette smoking should integrate trauma-informed approaches. Further, the results highlight early childhood and adolescence as particularly vulnerable periods with respect to the influence of physical abuse and neglect on cigarette smoking, pointing to the need for additional maltreatment prevention efforts during these developmental stages.